CYPERUS ROTUNDUS O`SIMLIGI O’SISH SHAROITI, KIMYOVIY TARKIBI VA XALQ TABOBATIDAGI O`RNI - Yigitaliyeva, Maxbubaxon; Xo’jayev , Vahobjon (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
In this article, general information about the Cyperus rotundus plant, its growth conditions, the plant's organs, the use of its root in folk medicine, its healing properties, and its ingredients are described.